C'est de la faute de Colette: L'Intertextualité dans trois ouvrages de Régine Detambel (La Modéliste, Le Jardin Clos, Elle ferait battre les montagnes) - Collett, Anne Elizabeth (French Language and Literature, 2024)
This study examines the intertextuality present in three works by Régine Detambel, a contemporary French writer. The works in question are La Modéliste, Le jardin clos and Elle ferait battre les montagnes. The traces of intertextuality in Detambel's works derive from the influence of Colette, who commenced her writing career at the tum of the 20th century a writer whose profound effect on Detambel caused her to devote her essay Colette - comme une Flore; comme un Zoo to a study of the botanical and zoological metaphors for the human body present in her precursor's work. The theoretical aspect of this study is based on Antoine Compagnon' s La Seconde Main which examines the role of the quotation in its broadest sense, as well as Gérard Genette's Palimpsestes, a study of the traces of one author's work in another's. Genette qualifies this terminology by naming the original text a hypotexte, while the transformation thus derived is called the hypertexte. The intertextuality present in Detambel's works is examined on both a literary and a thematic level. The former comprises a study of the quotation within its context as a metaphor derived from Colette's work and transformed by Detambel into a poetic form which transcends that of its origin. The power of the quotation to initiate dialogue - and dialectic - is also studied, together with the role of the reader in both the realisation and the completion of the text. Implicit in this examination is the role of the writer of this study, as reader of both Colette and Detambel. On a thematic level, we examine the concept of a triumphant and inviolable femininity which has its roots in a pagan vision of woman, one which predates any form of monotheistic religion. Colette's influence is also present as a literary style which is visceral and frank, while simultaneously qualifying for the epithet of 'prose poetry'. A female gaze which reverses the stereotypical prerogative of the male gaze is further evidence of Colette's influence. In her role as author, attention is drawn to the fact that Detambel, like Colette, has no declared intention with regard to the reader; her works are entirely non-didactic. It is this lack of intention, a hallmark of both authors' works which renders them universal. For both women, writing was a catalyst in the discovery of both their feminine nature and their writing potential, in a world which today differs little from that in which Balzac described aspirant women writers as "half-women; ones who might just as well be described as men." Two interviews conducted with Régine Detambel, revealed a writer and woman in no doubt as to her identity in both spheres. Like Colette, Detambel succeeds in triumphing over adversity precisely because of, (and not despite), a femininity which is inviolable - and inviolate. So closely does this image conform to that of Colette, that there is no question that Detambel's work is 'Colette's fault' - the irony of which lies in a reversal of the traditionally pejorative connotation of that phrase.